The Predibility of Asean-5 Exchange Rates - Liew, Khim Sen; Ahmad Zubaidi, Baharumshah (Universiti Malaysia Sarawak, 2000)
In an attempt to determine the predictability of Asean exchange rates, five currencies including Malaysian ringgit, Thailand baht, Singapore dollar, Indonesian rupiah and the Philippines peso, denominated in US dollar as well as Japanese yen, were modeled using advanced time series analysis. Results suggested that Singapore exchange rate could be better predicted when denominated in US dollar, most probably because the East Asian Financial Crisis did not affect them both. On the other hand, other Asean exchange rates were better predicted when denominated in Japanese yen, as they had closer economic ties with Japan. However, while Japan had undergone serious recession after the crisis, it did not experience dramatic political instability as experienced by Indonesia, hence Indonesian rupiah remained unpredictable by yen. These results show that although advanced time series analysis dealt with economic fundamentals implicitly; it still could be a powerful tool for exchange rates modeling and forecasting, especially in the medium to long term.